College algebra with trigonometry - Barnett, Raymond A. (McGraw-Hill, 2001)
The goal of this series is to emphasize computational skills, ideas, and problem solving rather than mathematical theory. "College Algebra with Trigonometry, 7/E", introduces a right angle approach to trigonometry and can be used in one or two semester college algebra with trig or precalculus courses. The large number of pedagogical devices employed in this text will guide a student through the course. Integrated throughout the text, the students and instructors will find Explore-Discuss boxes which encourage students to think critically about mathematical concepts. In each section, the worked examples are followed by matched problems that reinforce the concept that is being taught. In addition, the text contains an abundance of exercises and applications that will convince students that math is useful. A Smart CD is packaged with the seventh edition of the book. This CD reinforces important concepts, and provides students with extra practice problems.